Upaya Penanggulangan Pandemi Covid-19 di Panti Asuhan Al-Falah, Padang - Refinel Refinel; Emriadi Emriadi; Safni Safni; Mai Efdi; Syukri Syukri; Suryati Suryati; Marniati Salim; Imelda Imelda; Ibnu Irawan; Putri Arwanda (Warta Pengabdian Andalas, 2020)
The Islamic Boarding School and Orphanage Al-Falah Padang are located on Bypass Km 16, behind the West Sumatra TVRI office. Al-Falah Boarding School has 367 students, 265 of them are foster children in the Orphanage. Inadequate construction and classrooms, the students and foster children of the Islamic Boarding School and the Al-Falah Orphanage studied and lived their daily lives. The occurrence of the Covid-19 pandemic certainly affected the daily activities and learning activities of the orphanage children. Especially, the fulfillment of their basic needs. Moreover, the main problem of Covid-19 is not only about the effects by the virus on sufferers but also about its rapid transmission. Therefore, to help the crisis due to Covid-19, several lecturers and students from the Faculty of Mathematics and Natural Sciences Universitas Andalas (Unand) provided staple foods, money, masks, hand sanitizers, and disinfectants for residents of the Al-Falah Padang orphanage. It is hoped that can help the residents of the Al-Falah orphanage who certainly feel the impact of the Covid-19 pandemic.